Upper Gastrointestinal Foreign Body, our Experience in Faridpur Medical College Hospital (Faridpur Medical College Journal, 2020)
Accidental ingestion and impaction of food or non-food foreign body in upper GIT is not uncommon. This retrospective study was undertaken at Gastroenterology department of Faridpur Medical College Hospital, Bangladesh. Data were collected from endoscopy software by computer search among patients with foreign bodies in upper GIT from January 2012 to December 2018. Total 41 patients with endoscopically proved ingested with or without impacted foreign body in the upper GIT were studied. Of them, 28 were male and 13 were female with age ranges from 15 to 85 years with a mean age of 52.66 ± 19.7 years. Meat bolus was the commonest type (12; 29.3%), followed by dental prosthesis (9; 22%). Most of them (24; 58%) were impacted between 20 to 30 cm from incisor teeth. We could successfully remove 38 cases with a success rate of 92.7% with the help of dormia basket, polypectomy snare & rat tooth foreign body grasper. We found few erosions and superficial ulcerations at the impacted site among patients with dental prosthesis, pill with strip and chicken bone. One patient with sharp flat bone of hilsa fish was impacted at esophagus like sharp cutting blade and produced incised looking wound at both esophageal walls. In 19 cases (46.34%) we found definite anatomic abnormalities and 19 cases (46.34%) no abnormalities was found. Rest 3 cases, who were referred to surgeon we failed to know the underlying pathology. Sharp foreign bodies impacted at upper esophagus were difficult to remove endoscopically.Faridpur Med. Coll. J. Jul 2019;14(2): 74-78